Endocytic Rabs Are Recruited to the Trypanosoma cruzi Parasitophorous Vacuole and Contribute to the Process of Infection in Non-professional Phagocytic Cells - Salassa, Betiana Nebaí; Cueto, Juan Agustín; Gambarte Tudela, Julián; Romano, Patricia Silvia (Frontiers in Cellular and Infection Microbiology, 2020)
Trypanosoma cruzi is the parasite causative of Chagas disease, a highly disseminated illness endemic in Latin-American countries. T. cruzi has a complex life cycle that involves mammalian hosts and insect vectors both of which exhibits different parasitic forms. Trypomastigotes are the infective forms capable to invade several types of host cells from mammals. T. cruzi infection process comprises two sequential steps, the formation and the maturation of the Trypanosoma cruzi parasitophorous vacuole. Host Rab GTPases are proteins that control the intracellular vesicular traffic by regulating budding, transport, docking, and tethering of vesicles. From over 70 Rab GTPases identified in mammalian cells only two, Rab5 and Rab7 have been found in the T. cruzi vacuole to date. In this work, we have characterized the role of the endocytic, recycling, and secretory routes in the T. cruzi infection process in CHO cells, by studying the most representative Rabs of these pathways. We found that endocytic Rabs are selectively recruited to the vacuole of T. cruzi, among them Rab22a, Rab5, and Rab21 right away after the infection followed by Rab7 and Rab39a at later times. However, neither recycling nor secretory Rabs were present in the vacuole membrane at the times studied. Interestingly loss of function of endocytic Rabs by the use of their dominant-negative mutant forms significantly decreases T. cruzi infection. These data highlight the contribution of these proteins and the endosomal route in the process of T. cruzi infection.